(untitled) (Annals of Library and Information Studies, 2025)
Documentation of traditional knowledge (TK) has been given due importance internationally in the context of preservation and protection of one’s rights. Global discussions also focus on integrating multiple knowledge systems for nurturing and stimulating innovations in the context of sustainable use and conservation of natural resources. The article provides a glimpse of the efforts being pursued by the Council of Scientific and Industrial Research (CSIR), India for enhancing the scope of the Traditional Knowledge Digital Library (TKDL) by way of including India’s traditional agriculture information in the database. The vital factors for TK documentation include global initiatives on TK, information on traditional agriculture, patenting trends and innovation areas, data structure and ontology, among others. The article also highlights the synergy that can be drawn by bringing together TK, digital frameworks and sustainability science to address global challenges. Digital databases such as the TKDL can serve as important instruments towards the pursuit of sustainability science.